An Efficient Adjoint Sensitivity Analysis of Flexible Multibody Systems for a Level‐set‐based Topology Optimization. Issue 1 (25th January 2021) - Azari Nejat, Ali; Held, Alexander; Seifried, Robert
Abstract: For large‐scale topology optimization of flexible multibody systems, only little results exist. This is due to the complexity of the modeling of the flexible bodies and the big effort to provide exact gradients. The considered flexible multibody systems can undergo both large nonlinear motions as well as small elastic deformations. Here, the flexible components are modeled by the floating frame of reference approach. For gradient calculation, the fully coupled adjoint sensitivity analysis is used, which is a semi‐analytical approach based on variational calculus. The computational effort strongly corresponds to the number of design variables. In this work, a design space reduction using radial basis functions is performed and the gradient of flexible components is constructed based on its exact value on a subset of selected design elements. In order to show the substantial gain in computation time, the exact and approximated gradient of a flexible crank in a slider‐crank mechanism are computed and applied for a level‐set‐based topology optimization.